ESTETIKA HINDU DALAM CERITA SUNDA DAN UPASUNDA PADA TEKS ĀDIPARWA - Ida Bagus Subrahmaniam Saitya (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2018)
Ādiparwa is an early part of the Mahābhārata. Ādiparwa can be considered to consist of 2 (two) separate sections. The first part, presenting the framework of the Bhārata epic, is the story of the sacrifice on the order of Janamejaya in order to destroy the dragons because Parikṣit who was the father of Janamejaya was killed by the Taksaka. The second part, contains the genealogy of the Paṇḍawa and Korawa, their birth and youth to Arjuna’s marriage to Subhadrā. In addition to the above story, in Ādiparwa there are also stories about Sunda and Upasunda, the story is often used in Balinese art, especially in the ballet. Sunda and Upasunda are siblings who are very loyal, they get the grace to be able to master the tri Bhuwana of Bhaṭāra Brahmā. The Sundanese and Upasunda stories contain elements of Hindu aesthetics, namely Satyam, Siwam, and Sundaram.